1976
DOI: 10.1210/jcem-42-5-907
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay for Serum Thyroxine-Binding Globulin: Results in Normal Subjects and in Patients with Hepatocellular Carcinoma

Abstract: Serum thyroxine-binding globulin (TBG) was measured by radioimmunoassay. The human TBG used in this study was purified by affinity, anion-exchange, and gel filtration chromatography. The serum TBG concentration in 98 euthyroid normals was 1.48 +/- 0.46 mg/100 ml (mean +/- SD), which is one-half that previously reported using a similar method. The level in females (1.66 +/- 0.56) was significantly higher than that in males (1.37 +/- 0.37). Comparison of the serum TBG level and the maximum binding capacity of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
2

Year Published

1978
1978
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 10 publications
1
11
1
2
Order By: Relevance
“…Die radioimmunchemische zu einer Unsicherheit gegenüber der TBG-BestimBestimmung von TBG hat in den letzten Jahren im-mung geführt. Wir haben daher TBG erneut hochgemer mehr zu einer wertvollen Bereicherung in der reinigt und chemisch charakterisiert, worüber an anSchilddrüsendiagnostik selbst beigetragen (3,(8)(9)(10)(11)(12)(13)(14)(15)(16). derer Stelle berichtet wird.…”
Section: Einführungunclassified
See 1 more Smart Citation
“…Die radioimmunchemische zu einer Unsicherheit gegenüber der TBG-BestimBestimmung von TBG hat in den letzten Jahren im-mung geführt. Wir haben daher TBG erneut hochgemer mehr zu einer wertvollen Bereicherung in der reinigt und chemisch charakterisiert, worüber an anSchilddrüsendiagnostik selbst beigetragen (3,(8)(9)(10)(11)(12)(13)(14)(15)(16). derer Stelle berichtet wird.…”
Section: Einführungunclassified
“…Aus früheren präparativen Untersuchungen war schon bekannt, daß ein unterschiedliches Molekulargewicht von etwa 60000 + 3000 angegeben wurde (l, 4, 20, 21, 22 Theoretische Berechnungen lassen die Konzentration von zirkulierendem TBG im Serum bei 10 mg/1 erwarten (l, 21, 23). Die von anderen Autoren (9,10,31) radioimmunchemisch ermittelten Konzentrationen bei gesunden Probanden lagen nahe an diesem Erwartungswert, der auch mit unserer enzymimmunologischen Methode annäherungsweise gemessen wird. Von mehreren Autoren wurden aber teilweise wesentlich höhere Konzentrationen angegeben (6,3,11,32).…”
Section: Charakterisierung Des Tbgunclassified
“…Despite this, clinical evidence of hypothyroidism is uncommon and direct measurement of free T4 (fT4) or the free thyroxine index has usually given normal values (Green et al, 1970;Liewendahl et al, 1983). In contrast, hyperthyroxinaemia has been described in some patients with hepatocellular carcinoma (HCC), a frequent complication of long-standing cirrhosis (Gershengorn et al, 1976;Kalk et al, 1982;Nelson, 1979). The hyperthyroxinaemia has been attributed to elevated levels of thyroxine binding globulin (TBG) but whether abnormalities of other thyroid binding proteins such as albumin and prealbumin are also involved has not been determined.…”
mentioning
confidence: 99%
“…Previously Pederson (1974) had reported that hepatocellular carcinoma was occasionally associated with an increase in serum TBG. However, Gershengorn et al (1976) demonstrated that TBG was far from constant and was not correlated with the The relation between serum TBG and serum CEA was examined in many cancer patients, but no correlation was found (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%